Structural assessment and seismic response of the historic Justinian stone arch bridge - Zeki Özcan (Case Studies in Construction Materials, 2025)
The study focuses on the architectural and structural analysis of the Justinian Bridge, an ancient stone arch bridge dating from the Byzantine era, located on Turkey's Sakarya (Sangarius) River. The research examines the structural configuration of the bridge and integrates its architectural background with data derived from comprehensive analyses. Experimental geophysical investigations were employed to assess the bridge's structural behavior, particularly considering the depths of the piers embedded in alluvial soil layers. The studies provided valuable data on the geometric and hydraulic properties of the bridge piers. The bridge's natural vibration frequencies and mode shapes were determined using a three-dimensional finite element model under four different boundary conditions. The results revealed that natural vibration frequencies are sensitive to soil properties. Time history analysis, incorporating ten sets of ground motion data, evaluated the bridge's dynamic response to earthquake loads. The damage distribution on the bridge body was determined and compared with the stresses obtained from the numerical analysis. The numerical results accurately show the damaged areas of the bridge. The findings provide valuable insights into the safety of historic stone arch bridges and serve as an essential reference for future conservation efforts.